Some Polemical Observations on Utah's Cooperative Wildlife Management Unit Program - Eliason, Stephen L. (Scholarworks @ Morehead State, 2000)
Since the early 1990s, the state of Utah's Division of Wildlife Resources (DWR) has sponsored the Cooperative Wildlife Management Unit (CWMU) hunting program (Messmer et al. 1998). Under this program, landowners who meet certain requirements are allotted a specified number of big-game hunting permits and may designate hunters of their choice to receive them. In most instances, those hunters then pay a fee (generally thousands of dollars) to hunt on the private land. In exchange, landowners are required to allot a certain minimal number of permits (15% of the total buck mule deer [Odocoileus hemionus] and bull elk [Alces alces] permits) to the public via a drawing and to provide them free access to hunt on the land.